This is not my city - Bagina, Elena (project baikal, 2014)
The building boom that took place in Russia at the turn of the 20th century led to drastic changes in the architectural look of the cities, which had developed for centuries. Expansion of a new high-rise development resulted in misbalance between old and new.  Hence the historical cities are losing their identity. The majority of middle-aged and older population gives a negative estimate to the changes in their cities, which become unfamiliar to them.